Qualitative and Quantitative Neuropathology Approaches Using Magnetic Resonance Microscopy (Diffusion Tensor Imaging) and Stereology in a Hexachlorophene Model of Myelinopathy in Sprague-Dawley Rats. (December 2020) - Sills, Robert C.; Johnson, G. Allan; Anderson, Robert J.; Johnson, Crystal L.; Staup, Michael; Brown, Danielle L.; Churchill, Sheba R.; Kurtz, David M.; Cushman, Jesse D.; Waidyanatha, Suramya; Robinson, Veronica Godfrey; Cesta, Mark F.; et al.
It is well established that hexachlorophene, which is used as an antibacterial agent, causes intramyelinic edema in humans and animal models. The hexachlorophene myelinopathy model, in which male Sprague-Dawley rats received 25 to 30 mg/kg hexachlorophene by gavage for up to 5 days, provided an opportunity to compare traditional neuropathology evaluations with magnetic resonance microscopy (MRM) findings. In addition, stereology assessments of 3 neuroanatomical sites were compared to quantitative measurements of similar structures by MRM. There were positive correlations between hematoxylin and eosin and luxol fast blue stains and MRM for identifying intramyelinic edema in the cingulum of corpus callosum, optic chiasm, anterior commissure (aca), lateral olfactory tracts, pyramidal tracts (py), and white matter tracts in the cerebellum. Stereology assessments were focused on the aca, longitudinal fasciculus of the pons, and py and demonstrated differences between control and treated rats, as was observed using MRM. The added value of MRM assessments was the ability to acquire qualitative 3-dimensional (3-D) images and obtain quantitative measurements of intramyelinic edema in 26 neuroanatomical sites in the intact brain. Also, diffusion tensor imaging (fractional anisotropy [FA]) indicated that there were changes in the cytoarchitecture of the white matter as detected by decreases in the FA in the treated compared to the control rats. This study demonstrates creative strategies that are possible using qualitative and quantitative assessments of potential white matter neurotoxicants in nonclinical toxicity studies. Our results lead us to the conclusion that volumetric analysis by MRM and stereology adds significant value to the standard 2-D microscopic evaluations.